Sustainable illumination: Experimental and simulation analysis of illumination for workers wellbeing in the workplace - Saeed Shojaee Barjoee; Semyon Gendler (Heliyon)
Incorporating an illumination optimization plan into the worker safety management process in industrials is essential since the quality of workplace illumination has a significant impact on workers' well-being. The purpose of this study was to optimize illumination conditions in industrial workspaces using light-emitting diode (LED) technology with a color temperature of 6500 K and a CRI of 85 %. To accomplish this, the DIALux illumination simulation tool was utilized. It was validated using measured illumination data from a lux meter (ST-1300 model 1308). Four factors—the number of luminaires, the effective height of the luminaires, the illumination technology, and the light loss factor—were applied to configure sixteen simulation scenarios. Subsequently, eleven quadratic polynomial equations were proposed for estimating the changes in the average illumination in eleven workplaces using the multiple regression analysis technique on the simulatively prepared dataset. The final step was assessing the desirability degree of the suitable illumination scenario. It was discovered that the DIALux software's illumination simulation error percentage fell within an acceptable range. The illumination technology factor had the greatest impact on the average illumination of workplaces. The most impactful interaction terms of the factors were illumination technology and the number of luminaires. For every workplace, the optimized illumination's desirability degree was expected to be more than 0.9. The proposed approach yields promising results and can be a valuable tool for improving the illumination conditions of workers in industries.